Marine Benthic Diversity of the Gulf of Kutch, Gujarat: A review - Hatkar, Prachi; Vachhrajani, Kauresh; Kuppusamy, Sivakumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present paper reviews and compiles a list of benthic fauna in the Gulf of Kutch (GoK). The literature on the GoK coastal waters was reviewed from 1945 to 2024. The comprehensive literature review for this checklist paper was compiled from research articles, books, field guides and doctoral thesis, and reports from various searches. The scientific names of species were checked after cross-referencing species names with the WoRMS database. The benthic faunal comprises Gastropods, Bivalve, Scphalalopod, Polychaetes, Sipuncula, Echinoderm, Anomuran, Brachyuran, Isopods, Amphipods, Foraminiferans, Porifera, Anthozoan, Sea spiders, Nematodes, Platyhelminthes, Stomatopod from the Gulf of Kutch. The review presents an updated inventory detailed in the case of Gastropods (233 species, 61 families), Bivalves (123 species, 31 families), Five species of Scaphalopod belonging to two families, Placophora (two species, one family), Brachyurans (152 species, 30 families), Malacostrata (seven species, three families) Polychaetes (65 species, 28 families), Sipuncula (three species, two families), Amphipods (46 species, 20 families), Porifera (43 species, 28 families), Prawns and shrimps (45 species 14 families), Isopods (Two species, two families), Echinoderm (39 species, 23 families), two species of Platyhelminths belonging to single family, Cnidarian 13 species, seven families, Anomuran (hermit crab seven species belonging to one family), Sea slug and Nudibranch (46 species, 18 families), Nematodes (four species, four families), Foraminiferans (19 species, seven families). The lack of comprehensive data on the current macrobenthic faunal diversity status underscores the need for further research and expertise in this field.